Captain Underpants and the perilous plot of Professor Poopypants : the fourth epic novel - Pilkey, Dav, 1966- (London : Scholastic, 2001)
When Professor Pippy P. Poopypants comes to Jerome Horwitz Elementary School to teach science, and he goes off the deep end because students make fun of his name, only Captain Underpants can save the school from the professor's perilous plot.
On the title page, "Dav Pilkey" is crossed out.
English
Keywords: Cartoons and comics -- Fiction; Heroes -- Fiction; Humorous stories; School principals -- Fiction; Schools -- Fiction